Microeconomics, price theory in practice / Rogre Leroy Miller - Leroy Miller, Roger [et.] (1995)
An introduction to microeconomic reasoning, positive versus normative economics, chapter summary, trouble spots, review questions, price theory problems, writing exercise; demand and supply, a review, bargaining chapter summary, trouble spots, review questions, price theory problems, writing exercise; taxer and restrictions on price and quantity, the government and property rights, chapter summary, trouble spots, review questions, price theory problems, writing; budget and time constraints, the budget constraint, curved and kinkeed budget constraints, time constrainst chapter summary, trouble spots, review questions, price theory problems, writing exercise; individual preferences and optimal choice, the geovernment and property rights, chapter summary, troubles spots, review questions, price theory problems, writing exercise; budget and time constraints, chapter summary trouble spots, review questions, price theory problems, writing exercise; individual preferences and optimal choice, chepter summary , troble spots, review questions price theory problems, writing exercise; appendix 5a utility theory, math notepad, the lagrangian utility maximization problem; how price and income changes affect demand, changes in the relative price of one good, changes in income, income and substitution effevts, the compensated demand curve, price indices and the cosr of livieng, chapter summary, review questions; organization and management of the firm, nonprofit organizations, chapter summary, review questions, price theory problems, writing exercisi; production, production technology, isoquants, production in the long run, chapter summary, trouble spots, review questions, price theory problems writing exercise; costs, cost and production, short-run costs, short-run const curves, production costs inthe long run, comparing long-run and short-run costs curve, multiproduct firms and dynamic changes in costs, chapter summary, trouble spots, review questions price theory problems writing exercise, an analytical treatment of cost minimization, price-taking firms in compectitive markets, perfectly competitive markets, the perfectly competitive firm, the perfectly compectitive market in the short run, perfect compectitive inthelong run, efficiency of perfect competition; monopoly and market power, price and output decisions for a monopoly, origins of monopolies and market poewr, cartels, comparing a monopoly to a perfectly competitive market, detecting and preventing a monopoly, pricing strategies with market power, public policy toward price discrimination, a cripter summary, trouble spotr, review questions, price theory problems, writing execise; monopolistic competition, oligopoly, and game theory, estry deterrence, chapter summary, trouble sots, review questions, price theory problems, writing exercise; lobor and other factors of production, the demand for factors of production, factor supply,monopsony and union bargaining, searching for the best job offer, chapter summary, trouble spots; intertemporal markets and decision marking under uncertainty, consumption over time, determinants of interrets rates, markets for risk transfer; general equilibrium and voluntary exchange, general equilibrium analysis, voluntary exchange between individuals, efficient production the production possibilities frontier; marketfailure and externalities, what causes market inefficiency, pure public goods, externalities, chapter summary trouble spots.